Method for screening high-catalytic-activity nitrogen-doped graphene-loaded single-metal-atom ammonia synthesis catalyst

By constructing nitrogen-doped graphene-supported single-metal atom catalysts and calculating the relaxation configuration and energy of the catalysts using density functional theory, highly active catalysts were screened out, solving the problem of insufficient catalytic activity of nitrogen-doped graphene-supported single-metal atom catalysts in the ammonia synthesis reaction, and realizing an efficient and low-cost ammonia synthesis process.

CN120861114APending Publication Date: 2025-10-31HUBEI ENG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510769629.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-10
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

In the existing technology, there are few studies on the catalytic activity of nitrogen-doped graphene-supported single-metal atom catalysts in the ammonia synthesis reaction, and the reaction mechanism is unclear, which leads to the problems of high energy consumption and high cost in the ammonia synthesis process.

Method used

By constructing nitrogen-doped graphene structures and loading single metal atoms Co or Fe, the relaxation configuration and energy of the catalysts were calculated using density functional theory and VASP software. Highly active catalysts were screened, revealing the relationship between catalytic activity and metal atom type and coordination environment, and clarifying the reaction mechanism.

Benefits of technology

This provides a theoretical basis for designing efficient ammonia synthesis catalysts, reducing energy consumption and costs, improving catalyst development efficiency, and deepening the understanding of the microscopic mechanism of the ammonia synthesis reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120861114A_ABST
    Figure CN120861114A_ABST
Patent Text Reader

Abstract

The invention discloses a method for screening a high-catalytic-activity nitrogen-doped graphene-loaded single-metal-atom ammonia synthesis catalyst, and belongs to the technical field of ammonia synthesis. The method comprises the following steps: constructing an original graphene configuration; constructing a nitrogen-doped graphene configuration; a nitrogen-doped graphene loaded monometal configuration is constructed; the Eform is formed to judge the stability; constructing an adsorption configuration of reactant molecules; analyzing the relaxation configuration to judge the activation degree; the adsorption stability is judged according to the adsorption energy Eads; determining a path of N2 thermal reduction reaction; adopting NEB and Dimer methods to construct a transition state spatial configuration; reaction heat and activation energy are calculated, and activity differences of different catalyst surfaces are analyzed. Based on density functional theory calculation, catalyst screening standards with formation energy, adsorption energy and activation energy barriers as indexes are established, the high-activity catalyst is screened out theoretically, the experiment trial and error cost is reduced, and the catalyst development efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ammonia synthesis technology, specifically relating to a method for screening nitrogen-doped graphene-supported single-metal atom ammonia synthesis catalysts with high catalytic activity. Background Technology

[0002] With the continuous development of the global economy and the ongoing population growth, the demand for ammonia is showing an increasing trend. Therefore, exploring green and sustainable methods for ammonia synthesis has become a research hotspot and key task in the field of chemistry. Currently, industrial ammonia synthesis mainly relies on the Haber-Bosch process (N2 thermal reduction, N2TR). This traditional process, due to its dissociation mechanism, requires a large amount of energy to break the stable N≡N bonds, posing serious challenges from both energy utilization and economic cost perspectives.

[0003] In recent years, single-metal atom catalysts (SACs) have attracted widespread attention due to their unique physicochemical properties. These catalysts can significantly enhance the specific activity of catalytic reactions while reducing the loading of expensive noble metals, thereby lowering costs. Among the many materials suitable for supporting single metal atoms, graphene-based materials have become an ideal choice due to their excellent thermal stability, mechanical stability, and good electrical conductivity. Density functional theory (DFT) calculations suggest that nitrogen-doped graphene supporting a single transition metal atom may be a potential catalyst for the electrochemical reduction (N2ER) of N2 with low overpotential and high selectivity. However, there are relatively few studies on the catalytic activity of nitrogen-doped graphene-supported single-metal atom catalysts for N2TR. The specific reaction mechanism of this catalyst in the N2TR reaction remains unclear, and related research reports are scarce.

[0004] Therefore, it is urgent to use quantum chemistry and computational chemistry methods to conduct in-depth theoretical research on the role mechanism of nitrogen-doped graphene-supported single-metal atom catalysts in the N2TR reaction, so as to provide strong theoretical support for the design and screening of novel and efficient ammonia synthesis catalysts. Summary of the Invention

[0005] To address the shortcomings of existing technologies, one objective of this invention is to provide a method for screening highly catalytically active nitrogen-doped graphene-supported single-metal atom ammonia synthesis catalysts. Based on density functional theory and quantum chemistry, this invention constructs a nitrogen-doped graphene structure as the substrate material and supports single-metal atoms (Co or Fe) as the catalyst model. The adsorption behavior of H2 and N2 molecules on the catalyst surface is calculated, and catalysts with stable adsorption behavior are selected for further research on the N2TR catalytic mechanism. The influence of nitrogen-doped graphene-supported single-metal atom (Co or Fe) catalysts on the N2 thermal reduction (N2TR) ammonia synthesis reaction is studied in detail. The relationship between metal atom type, coordination environment, and catalytic activity is clarified, revealing the reaction mechanism and providing a theoretical basis for the design and development of high-performance ammonia synthesis catalysts. Ultimately, this will promote the development of ammonia synthesis processes towards greener and more efficient directions.

[0006] To achieve the above objectives, the specific technical solution of the present invention is as follows:

[0007] A method for screening nitrogen-doped graphene-supported single-metal atom ammonia synthesis catalysts with high catalytic activity includes the following steps:

[0008] Constructing the original graphene configuration;

[0009] One and two carbon atoms were removed from the original graphene configuration to form single-vacancy and double-vacancy defects, respectively. The carbon atoms surrounding the vacancy were replaced with nitrogen atoms to obtain two defect nitrogen-doped graphene configurations, N3 / G and N4 / G. The relaxation configuration and relaxation energy were obtained based on density functional theory and VASP software.

[0010] Single metal atoms M were loaded at the vacancies in the N3 / G and N4 / G configurations, respectively, to construct two nitrogen-doped graphene catalyst models with single metal atoms loaded in MN3 / G and MN4 / G configurations; the relaxation configurations and relaxation energies were obtained based on density functional theory and VASP software.

[0011] The formation energy E of the MN3 / G and MN4 / G catalyst models was calculated based on the relaxation energy. form , with E form To determine the stability of MN3 / G and MN4 / G catalysts and obtain the stable configuration of nitrogen-doped graphene supported on single metal atoms;

[0012] Based on the aforementioned relaxation configuration, spatial configurations for the adsorption of reactant molecules N2 and H2, as well as their co-adsorption, at different sites were constructed on the stable configurations of the MN3 / G and MN4 / G catalysts, and the adsorption energies E of reactant molecules at each adsorption site were obtained. adsTo determine the stability of reactant molecules adsorbed on the catalyst surface; and to determine the degree of activation of reactant molecules by comparing the degree of stretching of NN and HH bond lengths in the spatial configuration of reactant molecules before and after adsorption.

[0013] To construct the transition state spatial configuration in the N2 thermal reduction reaction process, targeting the most stable and highly activated spatial configuration of reactant molecules, the NEB and Dimer methods were used.

[0014] Calculate the heat of reaction and activation barrier for nitrogen reduction reactions in the *NHNH intermediate pathway and the *NNH2 intermediate pathway respectively, and obtain the optimal pathway and the activation barrier E of the rate-determining step. a ; Er of the rate-determining step in the optimal reaction pathway on the surface of different MN3 / G and MN4 / G catalysts a The values ​​were sorted by size to identify the most promising nitrogen-doped graphene-supported single-metal atom catalysts.

[0015] Preferably, the single metal atom M is Co and / or Fe. This is because the nitrogen-doped graphene-supported single metal atom catalysts that are experimentally stable and widely reported are all Co and Fe single metal atom catalysts.

[0016] Preferably, the nitrogen-doped graphene structure N3 / G contains 3 nitrogen atoms, and the nitrogen-doped graphene structure N4 / G contains 4 nitrogen atoms.

[0017] Preferably, based on density functional theory, the VASP software is used to select the generalized gradient approximation Perdew-Burke-Ernzerhof (PBE) functional as the exchange correlation energy functional to obtain the relaxation configuration and relaxation energy.

[0018] Preferably, the formation energy E of the MN3 / G and MN4 / G catalyst models is... form The calculation formula is as follows:

[0019]

[0020] In the formula, E[MN3 / G] and E[MN4 / G] are the total energy of the surface of nitrogen-doped graphene (N3 / G and N4 / G) after single metal atoms are loaded, respectively; E[G] is the energy of the original graphene; E[M] is the energy of the isolated single metal atom in the gas phase; and µ[C] and µ[N] are the chemical potentials of C atoms and N atoms, respectively, defined as half the energy of a single C atom and half the energy of a nitrogen molecule in the graphene configuration.

[0021] Preferred, with E form < 0 eV was used as the initial condition for screening catalysts to determine the stability of MN3 / G and MN4 / G catalysts.

[0022] Preferably, the adsorption energies E of the reactant molecules N2, H2, and their co-adsorption at different adsorption sites on the catalyst surface are... ads The calculation formula is as follows:

[0023]

[0024] In the formula, E(N2-MN) x / G), E(H2-MN) x / G) and E(N2+H2-MN x / G) represent the total energy of N2 and H2 molecules, and the energy of both co-adsorbed on the surface of nitrogen-doped graphene (MN3 / G and MN4 / G), respectively. x / G) represents the total energy of single metal atoms loaded on the surface of nitrogen-doped graphene (MN3 / G and MN4 / G), and E(N2) and E(H2) are the energies of ground-state N2 and H2 molecules in the gas phase, respectively.

[0025] Preferred, with E ads (N2+H2) < -1.0 eV was used as the second condition for screening catalysts to determine the stability of reactant molecules adsorbed on the surfaces of MN3 / G and MN4 / G catalysts.

[0026] The preferred, optimal reaction pathway and the activation energy barrier E of the rate-determining step a The calculation formula is as follows:

[0027]

[0028] In the formula, E(TS) is the energy of the transition state configuration in each elementary step, and E(IS) is the energy of the initial state configuration in each elementary step.

[0029] To gain a deeper understanding of the differences in the thermocatalytic nitrogen reduction reaction on nitrogen-doped graphene surfaces supported by different single metal atoms, this invention also provides an analytical method for understanding the mechanism by which the loading of single metal atoms affects the thermocatalytic ammonia synthesis reaction on nitrogen-doped graphene, thereby obtaining the effect of the type of loaded metal on MN. x The influence of / G on the performance of the ammonia synthesis reaction is investigated. The analytical methods mainly include the following steps:

[0030] Calculate different MN x The changes in the length of NN bonds in the intermediate configuration during the thermocatalytic nitrogen reduction reaction on the / G surface were compared to investigate the differences in the activation ability of different surfaces for NN bonds during the reaction.

[0031] Calculate different MN xThe activation energy barriers of each elementary process in the optimal pathway of the / G surface thermocatalytic nitrogen reduction reaction were quantitatively explored to investigate the influence of different supported metals on the thermocatalytic ammonia synthesis reaction of this type of catalyst.

[0032] Calculate different MN x The magnetic moments of the same intermediate configurations involved in the optimal pathway during the thermocatalytic nitrogen reduction reaction on the / G surface are analyzed, and their magnitudes are considered in relation to MN. x The effect of / G on the performance of the ammonia synthesis reaction.

[0033] In the method proposed in this invention, three general "descriptors" are selected for screening catalysts with single metal atoms supported on nitrogen-doped graphene:

[0034] (1) Formation energy (E) of MN3 / G and MN4 / G catalyst models form From a thermodynamic perspective, the formation energy of nitrogen-doped graphene systems loaded with single metal atoms should be negative, and the more negative the value, the more stable the system.

[0035] (2) The adsorption energy (E) of the co-adsorption of reactants N2 and H2 molecules on the catalyst surface ads The more negative the adsorption energy value, the more stable the system is after the reactants are adsorbed on the catalyst surface.

[0036] (3) Activation energy barrier (E) of the rate-determining step in the thermocatalytic nitrogen reduction reaction process of MN3 / G and MN4 / G type catalysts a When the rate-determining step E on the catalyst surface a The smaller the value, the better the catalytic performance of the catalyst surface. By evaluating the values ​​of the three parameters of each catalyst system, the most promising thermocatalytic ammonia synthesis catalysts are screened, ultimately achieving efficient and low-cost catalyst design and screening.

[0037] Compared with the prior art, the advantages of the present invention are:

[0038] (1) Based on density functional theory calculations, this invention establishes a catalyst screening standard with formation energy, adsorption energy and activation energy barrier as indicators, theoretically screens out highly active catalysts, reduces experimental trial and error costs and improves catalyst development efficiency.

[0039] (2) This invention reveals the influence of metal atom type (Co, Fe, etc.) and metal atom coordination environment (tri-coordination, tetra-coordination) on the catalytic activity of thermocatalytic nitrogen reduction reaction through theoretical calculations, providing a clear direction for the design of MN3 / G and MN4 / G type catalysts.

[0040] (3) The present invention elaborates in detail on MN xThe specific mechanism of the surface thermocatalytic nitrogen reduction reaction of / G provides theoretical support for experimental research, promotes the understanding of the microscopic mechanism of ammonia synthesis reaction, and has a certain degree of universality. Attached Figure Description

[0041] Figure 1 Nitrogen-doped graphene loaded with single metal atoms (MN) x Flowchart for screening catalysts for thermocatalytic ammonia synthesis reaction of type / G materials;

[0042] Figure 2 Top and side views of the relaxation configurations of nitrogen-doped graphene (N3 / G and N4 / G);

[0043] Figure 3 Top and side views of the relaxation configurations of nitrogen-doped graphene loaded with single metal atoms (MN3 / G and MN4 / G, M = Co, Fe);

[0044] Figure 4 Top and side views of the relaxation configurations of N2, H2, and both co-adsorbed on the MN4 / G (M = Co, Fe) surface;

[0045] Figure 5 Top and side views of the relaxation configurations of N2, H2, and both co-adsorbed on the MN3 / G (M = Co, Fe) surface;

[0046] Figure 6 For possible pathways in the thermocatalytic nitrogen reduction reaction on the MN3 / G (M = Co, Fe) surface, the elementary steps involved in the *NHNH intermediate pathway are marked by steps B1-B12, while steps C1-C9 correspond to the *NNH2 intermediate pathway, and steps A1-A9 belong to the same elementary steps of N2TR; in addition, orange and green are used to indicate intermediates that only appear on the CoN3 / G and FeN3 / G surfaces, respectively;

[0047] Figure 7 The reaction potential energy curve for the thermal catalytic reduction of N2 to ammonia on the CoN3 / G surface;

[0048] Figure 8 The reaction potential energy curve for the thermal catalytic reduction of N2 to ammonia on the FeN3 / G surface;

[0049] Figure 9 The optimal path for the thermocatalytic nitrogen reduction reaction on the CoN3 / G and FeN3 / G surfaces involves changes in the length of the N-N bond in the intermediate configuration;

[0050] Figure 10 The activation energy barriers for each elementary process in the optimal pathway of the thermocatalytic nitrogen reduction reaction on the CoN3 / G and FeN3 / G surfaces;

[0051] Figure 11 Spin density distributions of *NHNH and intermediates containing two *NH2 substances formed on the surfaces of CoN3 / G and FeN3 / G, with isosurfaces at 0.025 e / Å. 3 . Detailed Implementation

[0052] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0053] In this embodiment, single metal atoms Co and Fe were respectively supported on the surfaces of two types of nitrogen-doped graphene (N3 / G and N4 / G) to form four catalyst surfaces: CoN3 / G, FeN3 / G, CoN4 / G, and FeN4 / G. These four surfaces were used as research objects, and the activity and selectivity of the thermocatalytic ammonia synthesis reaction were studied on different surfaces. This study aimed to theoretically investigate the role mechanism of nitrogen-doped graphene-supported single metal atom catalysts in the N2TR reaction. The main steps included:

[0054] 1. Catalyst model construction and stability analysis

[0055] (1) The spatial configuration card of bilayer graphene was obtained through the Material Project website. The spatial configuration is hexagonal, and its cell parameters are a=b=2.46Å, c=6.8 Å 0, α=β=90°, γ=120°.

[0056] (2) The original graphene (G) spatial configuration was constructed using Material Studio software. The upper layer of the bilayer graphene was removed, and the initial unit cell was expanded by 4 × 4. The system contains a total of 32 carbon atoms.

[0057] (3) Using Material Studio software, nitrogen-doped graphene (N3 / G and N4 / G) spatial configurations were constructed. One and two carbon atoms were removed from the original graphene configurations, respectively, to form single-vacancy and double-vacancy defects. The carbon atoms surrounding the vacancies were replaced with nitrogen atoms to obtain two defect nitrogen-doped graphene structures, N3 / G and N4 / G. The number of nitrogen atoms doped in the N3 / G and N4 / G configurations were 3 and 4, respectively.

[0058] (4) The spatial configurations of single metal atoms (Co and Fe) loaded on nitrogen-doped graphene surfaces were also created using Material Studio software, forming four catalyst surfaces: CoN3 / G, FeN3 / G, CoN4 / G, and FeN4 / G. The creation of these surface configurations required the addition of a 15 Å vacuum layer along the normal direction to eliminate interactions between periodic layer interfaces.

[0059] (5) Once the above configuration file is prepared, use VESTA software to convert it from a CIF file type to the POSCAR type required for calculation. Then, use VASP calculation software based on first principles to optimize the catalyst surface, with the aim of obtaining the stable configuration and energy after relaxation (i.e., the relaxation configuration and relaxation energy).

[0060] (6) After configuration optimization, the top and side views of the relaxation configurations of nitrogen-doped graphene (N3 / G and N4 / G) are obtained as follows: Figure 2 As shown in the figure, the data represent the bond lengths between different atoms, in Å. It can be seen from the figure that the average bond length of the N-N bonds in the N3 / G configuration (2.590 Å) is slightly lower than that in the N4 / G configuration (2.713 Å), indicating that the interaction between N atoms in N3 / G is stronger than that on the N4 / G surface. Top and side views of the relaxation configurations of nitrogen-doped graphene loaded with single metal atoms (MN3 / G and MN4 / G, M = Co, Fe) are shown below. Figure 3 As shown in the figure, the data represents the bond lengths between different atoms, in Å. The figure reveals that when a single metal atom (Co or Fe) occupies a vacancy in the nitrogen-doped graphene configuration, the vertical distance between the metal atom and the graphene plane differs in MN3 / G and MN4 / G. For MN4 / G, the original graphene retains its planar structure, with the metal atom bonded to four surrounding N atoms in a four-coordinate configuration. The Co-N bond length is 1.877 Å, slightly shorter than the Fe-N bond in FeN4 / G (1.892 Å). In contrast, the two MN3 / G surfaces exhibit a non-planar configuration, where the three-coordinated Co and Fe atoms occupy positions approximately 1.4 and 1.5 Å above the graphene surface, respectively, and the Co-N bond is also shorter than the Fe-N bond. This difference in spatial configuration between MN3 / G and MN4 / G is the primary reason for the subsequent adsorption stability of reactant molecules on these two types of surfaces.

[0061] (7) The relaxation energy obtained after configuration optimization, and the formation energy E based on the MN3 / G and MN4 / G catalyst models. form The calculation formula, the calculated E form The values ​​are: CoN3 / G: -1.79 eV, FeN3 / G: -1.50 eV, CoN4 / G: -4.32 eV, FeN4 / G: -3.98 eV. formThe calculation method is as follows:

[0062]

[0063] Where E[MN3 / G] and E[MN4 / G] are the total energy of the surface of nitrogen-doped graphene (N3 / G and N4 / G) after single metal atoms are loaded, E[G] is the energy of the original graphene, E[M] is the energy of the isolated single metal atom in the gas phase, and µ[C] and µ[N] are the chemical potentials of C and N atoms, respectively, defined as half the energy of a single C atom and half the energy of a nitrogen molecule in the graphene configuration.

[0064] To form energy E form To evaluate the stability of catalysts supported on nitrogen-doped graphene surfaces by single-metal atoms, E form <0 eV was used as the initial condition and basis for screening catalysts. Therefore, in this embodiment, the four catalysts CoN3 / G, FeN3 / G, CoN4 / G and FeN4 / G all have good stability.

[0065] 2. Study on the adsorption properties of reactant molecules

[0066] (1) Based on the above relaxation configuration, four stable surfaces, CoN3 / G, FeN3 / G, CoN4 / G and FeN4 / G, were used as catalyst models. The spatial configurations of N2 and H2 adsorbed at different sites and co-adsorbed by the two were constructed using Material Studio software.

[0067] (2) After preparing the above configuration file, use VESTA software to convert it from a CIF file type to the POSCAR type required for calculation. Optimize the configuration using VASP software based on first-principles calculations, and obtain the relaxed configuration as follows: Figure 4 and Figure 5 As shown, the data in the figure includes bond lengths between different atoms, in Å, and adsorption energies (E) of reactant molecules. ads (Unit: eV). For the adsorption of H2 or N2 molecules on the catalyst surface, there are two different adsorption configurations: vertical adsorption and horizontal adsorption, distinguished by the prefixes α and β. For the αH2 adsorption configuration, H2 molecules are adsorbed on the CoN4 / G and FeN4 / G surfaces through a single MH bond (M=Co, Fe). Figure 4The bond lengths of the MH bonds (a and 4c) are 2.618 Å and 2.578 Å, respectively. Their relatively long bond lengths indicate a weak interaction between H2 and the surface. Furthermore, the bond lengths of the HH bonds after adsorption are 0.757 Å and 0.755 Å, respectively, which are almost unchanged compared to the bond length in the ground-state H2 molecule in the gas phase (0.751 Å), indicating a weak activation degree of the H2 molecule on the surface. For the βH2 adsorption configuration, the H2 molecule is adsorbed onto the surface through two MH bonds, where the HH bonds are stretched to 0.779 Å (CoN4 / G, as shown in the image). Figure 4 b) and 0.927 Å (FeN4 / G, such as Figure 4 d), its activation degree is stronger than that of the αH2 adsorption configuration. Conversely, the adsorption of N2 molecules, taking the αN2 adsorption mode, results in a more pronounced stretching of the NN bond. From the ground-state gaseous N2 molecule before adsorption, the 1.117 Å is stretched to 1.130 Å (CoN4 / G, as shown in the image). Figure 4 e) and 1.142 Å (FeN4 / G, such as Figure 4 g). However, only one configuration exists for the co-adsorption of the two, such as Figure 4 As shown in i and 4j, after N2 and H2 molecules adsorb, the NN bonds and HH bonds show no significant stretching compared to their gaseous counterparts, indicating that their activation levels are relatively weak. Using a similar analytical method, the relaxation configurations of H2, N2, and both co-adsorbed on the CoN3 / G and FeN3 / G surfaces are shown in... Figure 5 As shown, H2 molecules tend to adopt the βH2 adsorption configuration, which has a stronger activation effect, while N2 molecules tend to adopt the αN2 adsorption configuration. However, it is worth noting that the activation degree of N2 and H2 on the MN3 / G type surface is significantly stronger than that on the MN4 / G surface.

[0068] (3) The relaxation energy obtained after configuration optimization is based on the adsorption energy E of reactant molecules (N2, H2 and their co-adsorption) at different adsorption sites on the catalyst surface. ads The calculation formula is used to calculate the adsorption energy data for different adsorption sites, which are then labeled. Figure 4 and Figure 5 In the middle. Adsorption energy E ads The calculation method is as follows:

[0069]

[0070] Among them, E(N2-MN) x / G), E(H2-MN) x / G) and E(N2+H2-MN x / G) represent the total energy of N2 and H2 molecules, and the energy of both co-adsorbed on the surface of nitrogen-doped graphene (MN3 / G and MN4 / G), respectively. x / G) represents the total energy of single metal atoms loaded on the surface of nitrogen-doped graphene (MN3 / G and MN4 / G), and E(N2) and E(H2) are the energies of ground-state N2 and H2 molecules in the gas phase, respectively.

[0071] With adsorption energy E ads The stability of reactant molecules adsorbed on the surfaces of MN3 / G and MN4 / G catalysts is determined by E. ads (N2+H2) < -1.0 eV was used as the second condition for catalyst screening. The most stable configurations of N2 and H2 co-adsorbed on the CoN4 / G and FeN4 / G surfaces were calculated (e.g., Figure 4 The adsorption energies of i and 4j are -0.21 eV and -0.22 eV, respectively, while the most stable adsorption configurations on the CoN3 / G and FeN3 / G surfaces (e.g., i and j) are the most stable adsorption configurations. Figure 5 The adsorption energies of h and 5j are -1.40 eV and -1.87 eV, respectively. For the same reactant molecules, using the same adsorption mechanism, the adsorption strength and activation degree of the MN4 / G surface for reactant molecules are relatively low, indicating that reactant molecules are easily desorbed from the catalyst surface, which is unfavorable for subsequent nitrogen reduction reactions. Therefore, in the subsequent study of the thermocatalytic nitrogen reduction reaction mechanism, only the CoN3 / G and FeN3 / G surfaces with strong adsorption performance for reactant molecules will be considered.

[0072] 3. Reaction Mechanism and Catalytic Activity Analysis

[0073] (1) The transition state spatial configuration of the reactant molecules with the most stable adsorption and the strongest activation was constructed using the NEB and Dimer methods. For the CoN3 / G and FeN3 / G surfaces, the most stable configuration for co-adsorption of N2 and H2 was the αN2+βH2 configuration. Therefore, the subsequent N2 thermal reduction reaction process was studied using this adsorption configuration as the initial structure.

[0074] (2) According to the two common reduction mechanisms in the nitrogen thermal reduction reaction, these include the direct dissociation mechanism and the association mechanism. The dissociation mechanism refers to the direct breakage of the NN bonds in nitrogen molecules adsorbed on the catalyst surface to form two *N atoms before the hydrogenation of N2. On the CoN3 / G surface, the dissociation of N2 into two *N atoms via αN2 or βN2 adsorption requires the absorption of 5.36 eV and 5.22 eV of heat, respectively; on the FeN3 / G surface, this dissociation process requires the absorption of 4.14 eV and 3.88 eV of heat. The heat required for these processes is relatively high; therefore, from a thermodynamic perspective, the direct dissociation mechanism is unlikely to occur on MN3 / G type surfaces.

[0075] (3) For the association mechanism, it refers to the N2 * First hydrogenated to NNH* The N-N bond breaks after the species is formed. The association mechanism can be further subdivided into the *NHNH intermediate pathway and the *NNH2 intermediate pathway, such as... Figure 6 As shown, the transition state spatial configuration of the constructed N2 thermal reduction (N2TR) reaction process is optimized using the NEB and Dimer methods to obtain the relaxation configuration and relaxation energy. Then, the heat of reaction and activation energy barrier of the nitrogen reduction reaction process in different pathways are calculated. The activation energy barrier E of the optimal reaction pathway and the rate-determining step are shown. a The calculation method is as follows:

[0076]

[0077] Where E(TS) is the energy of the transition state configuration in each elementary step, and E(IS) is the energy of the initial state configuration in each elementary step.

[0078] For the CoN3 / G surface, the reaction potential energy curve for the thermal catalytic reduction of N2 to ammonia is shown in the figure below. Figure 7 As shown. The hydrogenation of NHNH2* to form the NH2NH2* intermediate (step B5) is the rate-determining step of the *NHNH intermediate pathway, requiring the overcoming of an activation energy barrier of 1.47 eV; the hydrogenation of NNH* to form the NNH2* intermediate (step C1, E...) a The rate-determining step (eV = 1.42 eV) is the *NNH2 intermediate pathway. Although the activation barriers of the rate-determining steps for both pathways are similar, the NH3 product generated via the *NHNH intermediate pathway is more readily produced than that via the *NNH2 intermediate pathway because the N*+NH2* intermediate generated from the NN cracking in the NNH2* intermediate has poor stability. Therefore, the optimal pathway for the thermal catalytic reduction of N2 to ammonia on the CoN3 / G surface is the *NHNH intermediate pathway, with an activation barrier of 1.47 eV for the rate-determining step.

[0079] For the FeN3 / G surface, the reaction potential energy curve for the thermal catalytic reduction of N2 to ammonia is shown in the figure below. Figure 8 As shown, the optimal pathway for the thermocatalytic reduction of N2 to ammonia is also the *NHNH intermediate pathway. The first hydrogenation step of N2* (step A6), which produces the NNH* intermediate, is the rate-determining step in the optimal pathway, and the calculated activation energy barrier is 1.25 eV.

[0080] (4) To gain a deeper understanding of the differences in catalytic activity between the two MN3 / G surfaces, the changes in the length of the NN bonds in the intermediate configurations during the optimal path of the thermocatalytic nitrogen reduction reaction on the CoN3 / G and FeN3 / G surfaces were compared (e.g., Figure 9As shown, during hydrogenation, the NN bonds are gradually stretched. For the same intermediate, the NN bond length on FeN3 / G is generally longer than that on the CoN3 / G surface. In particular, when the NHNH2* intermediate is formed, the breaking of NN bonds can be observed on the FeN3 / G surface, while on the CoN3 / G surface, NN breaking only occurs after the formation of the NH2NH2* intermediate. Accordingly, NH* species exist only on the FeN3 / G surface. Furthermore, by comparing the activation barrier values ​​of each elementary process in the optimal pathway of the thermocatalytic nitrogen reduction reaction on the CoN3 / G and FeN3 / G surfaces (e.g., ...), the results show that... Figure 10 As shown in the figure, the FeN3 / G surface exhibits a lower activation energy barrier in most hydrogenation processes prior to NN breakage. Therefore, for the same type of catalyst surface (MN3 / G), the FeN3 / G surface demonstrates relatively better catalytic activity for thermocatalytic nitrogen reduction.

[0081] (5) To obtain the type of loaded metal for MN x The influence of FeN3 / G on the performance of ammonia synthesis was investigated, and the electronic structure of intermediates involved in the N2TR reaction on the FeN3 / G catalyst surface was further studied. All reaction intermediates formed on the FeN3 / G surface possessed spin-polarized states, with calculated magnetic moments not less than 1.0 µB. In contrast, except for *NHNH and intermediates containing two *NH2 substances, the intermediates formed on the CoN3 / G surface were mostly non-spin-polarized states. Figure 11 The spin density distributions of *NHNH and intermediates containing two *NH2 substances formed on the surfaces of CoN3 / G (left) and FeN3 / G (right) are shown, with the isosurface at 0.025 e / Å. 3 The spin density is mainly distributed around the metal atoms, meaning the magnetic moment is primarily contributed by Co and Fe atoms. More specifically, the magnetic moment on the FeN3 / G surface containing *NHNH and two types of *NH2 is 3.0 µB, while the magnetic moment on the CoN3 / G surface is relatively small, only 2.0 µB. Therefore, compared to CoN3 / G, FeN3 / G intermediates tend to adopt a high-spin polarization state during the N2TR reaction. The Fe metal atoms with high spin polarization can greatly promote the adsorption and activation of N2 molecules, thus the FeN3 / G surface exhibits relatively better catalytic activity in the thermocatalytic nitrogen reduction reaction.

[0082] 4. MN x Screening and application of G-type catalysts

[0083] Taking MN into consideration x Formation energy (E) of the / G catalyst model form The adsorption energy (E) of the co-adsorption of reactants N2 and H2 molecules on the catalyst surface. ads) and MN x The activation barrier (E) of the rate-determining step in the thermocatalytic nitrogen reduction reaction process using catalyst G. a Three general "descriptors" are used to summarize nitrogen-doped graphene loaded with single metal atoms (MN). x Screening flowchart for thermocatalytic ammonia synthesis catalysts of type / G) materials (e.g.) Figure 1 As shown in the figure, among the four catalyst surfaces of CoN3 / G, FeN3 / G, CoN4 / G, and FeN4 / G, the FeN3 / G surface was identified as the most promising MN catalyst for the N2TR reaction. x The / G type catalyst can guide the experimental synthesis of FeN3 / G materials and apply them to the thermocatalytic nitrogen reduction to ammonia synthesis reaction to verify their excellent catalytic activity, thereby significantly reducing time and economic costs.

[0084] Based on the analysis of the above embodiments, this method can subsequently predict the catalytic activity of other metal-supported catalysts on nitrogen-doped graphene surfaces in the NRR reaction, which can reduce the high operating costs of experimental equipment and materials, save researchers a lot of time, and provide strong theoretical support for subsequent experiments.

[0085] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for screening nitrogen-doped graphene-supported single-metal atom ammonia synthesis catalysts with high catalytic activity, characterized in that, Includes the following steps: Constructing the original graphene configuration; One and two carbon atoms were removed from the original graphene configuration to form single-vacancy and double-vacancy defects, respectively. The carbon atoms surrounding the vacancy were replaced with nitrogen atoms to obtain two nitrogen-doped graphene configurations, N3 / G and N4 / G. The relaxation configuration and relaxation energy were obtained based on density functional theory and VASP software. Single metal atoms M were loaded at the vacancies in the N3 / G and N4 / G configurations, respectively, to construct two nitrogen-doped graphene catalyst models with single metal atoms loaded in MN3 / G and MN4 / G configurations; the relaxation configurations and relaxation energies were obtained based on density functional theory and VASP software. The formation energy E is calculated based on the relaxation energy. form , with E form Determine the stability of the catalyst and obtain a stable configuration; By constructing spatial configurations at different sites for the adsorption of reactant molecules N2 and H2, as well as their co-adsorption, on a stable configuration, the adsorption energy E of the reactant molecules was obtained. ads To determine the stability of reactant molecules adsorbed on the catalyst surface; The degree of activation of reactant molecules is determined by comparing the stretching of NN and HH bond lengths in the spatial configuration of reactant molecules before and after adsorption. To construct the transition state spatial configuration in the N2 thermal reduction reaction process, targeting the most stable and highly activated spatial configuration of reactant molecules, the NEB and Dimer methods were used. Calculate the heat of reaction and activation barrier for nitrogen reduction reactions in the *NHNH and *NNH2 intermediate pathways respectively, and obtain the optimal pathway and the activation barrier E of the rate-determining step. a ; Er of the rate-determining step in the optimal reaction pathway on the surface of different MN3 / G and MN4 / G catalysts a The values ​​were sorted by size to identify the most promising nitrogen-doped graphene-supported single-metal atom catalysts.

2. The method according to claim 1, characterized in that, The single metal atom M is Co and / or Fe.

3. The method according to claim 1, characterized in that, In the nitrogen-doped graphene structure N3 / G, the number of doped nitrogen atoms is 3, and in the nitrogen-doped graphene structure N4 / G, the number of doped nitrogen atoms is 4.

4. The method according to claim 1, characterized in that, Based on density functional theory, using VASP software, the PBE functional was selected as the exchange-correlation energy functional to obtain the relaxation configuration and relaxation energy.

5. The method according to claim 1, characterized in that, The formation energy E of the MN3 / G and MN4 / G catalyst models form The calculation formula is as follows: ; In the formula, E[MN3 / G] and E[MN4 / G] are the total energy of the surface of nitrogen-doped graphene (N3 / G and N4 / G) after single metal atoms are loaded, respectively; E[G] is the energy of the original graphene; E[M] is the energy of the isolated single metal atom in the gas phase; and µ[C] and µ[N] are the chemical potentials of C atoms and N atoms, respectively, defined as half the energy of a single C atom and half the energy of a nitrogen molecule in the graphene configuration.

6. The method according to claim 1, characterized in that, With E form < 0 eV was used as the initial condition for screening catalysts to determine the stability of MN3 / G and MN4 / G catalysts.

7. The method according to claim 1, characterized in that, The reactant molecules N2 and H2, and their adsorption energies E at different adsorption sites on the catalyst surface, are described. ads The calculation formula is as follows: ; In the formula, E(N2-MN) x / G), E(H2-MN) x / G) and E(N2+H2-MN x / G) represent the total energy of N2 and H2 molecules, and the energy of both co-adsorbed on the surface of nitrogen-doped graphene (MN3 / G and MN4 / G), respectively. x / G) represents the total energy of single metal atoms loaded on the surface of nitrogen-doped graphene (MN3 / G and MN4 / G), and E(N2) and E(H2) are the energies of ground-state N2 and H2 molecules in the gas phase, respectively.

8. The method according to claim 1, characterized in that, With E ads (N2+H2) < -1.0 eV was used as the second condition for screening catalysts to determine the stability of reactant molecules adsorbed on the surfaces of MN3 / G and MN4 / G catalysts.

9. The method according to claim 1, characterized in that, The optimal reaction pathway and the activation energy barrier E of the rate-determining step a The calculation formula is as follows: ; In the formula, E(TS) is the energy of the transition state configuration in each elementary step, and E(IS) is the energy of the initial state configuration in each elementary step.

Citation Information

Cited By

  • Directional design and screening method of nitrogen-doped MXene supported non-noble electrocatalyst for hydrogen fuel cell

    CN121565301A